TECHNOLOGICAL TECHNIQUES OF Al-Al2O3 MICROSTRUCTURES FORMATION FOR POWERFUL ELECTROMECHANICAL SYSTEMS - V. A. Sokol; D. L. Shimanovich; G. V. Litvinovich (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
Thus, Al-Al2O3 structures characteristic features of which are the considerable height (300 - 450 μm ) of contact pads and conducting lines, the high thickness (150 - 600 μm ) of insulating anodic alumina with high breakdown voltages between the contact pads (up to 8 kV) were made in the present work. Such structures may be used in power electromechanical systems. Methods of the high-speed anodization, of the deep anodization and chemical etching were investigated to provide practically vertical walls in the Al-Al2O3 system.